Optimalisasi Penggunaan Media Audio Visual dalam Pembelajaran Fikih: Studi Kasus pada Materi Shalat Jama' dan Qasar - Lia Rosidawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the use of audio-visual media in learning Fiqh on the material of jama' and qasar prayers at MI Sirojuttholibin. The learning process at this madrasah utilizes various available facilities and infrastructure, such as projectors, speakers, computers, and laptops, to support the learning process. With the use of audio-visual media, it is expected that grade III students can understand and practice the material of jama' and qasar prayers well. The research method used is qualitative, with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the use of audio-visual media, such as videos, during the learning process can help students understand and practice the implementation of jama' and qasar prayers correctly.